2011
DOI: 10.1111/j.1540-8175.2010.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Adolescence is Associated with Left Ventricular Hypertrophy and Hypertension

Abstract: Obese adolescents have a significantly higher prevalence of HTN and LVH. Our analysis suggests a direct negative effect of obesity on cardiovascular function starting early in teenage years. (Echocardiography 2011;28:150-153).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Hypertension has become more prevalent in the young adult population[10], and has been shown to cause increased LVM and even heart failure if left untreated[32]. With proper antihypertensive therapy LVH can regress and left ventricular dysfunction can improve[33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension has become more prevalent in the young adult population[10], and has been shown to cause increased LVM and even heart failure if left untreated[32]. With proper antihypertensive therapy LVH can regress and left ventricular dysfunction can improve[33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular hypertrophy (LVH) has a significant prevalence in the general population with some estimates approaching 16%-20% in population based samples[5,6], and up to 50% in those with hypertension[7-9]. As a result of the obesity epidemic, even the adolescent population has had a higher incidence of hypertension and LVH[10], with some estimates showing LVH in nearly 30% of younger hypertensive[11]. Thus, with the high prevalence of LVH that extends even into the young population and the increased cardiovascular risk it confers, it is important to identify patients with increased LVM so that they may receive appropriate care.…”
Section: Introductionmentioning
confidence: 99%
“…A number of cross sectional studies have identified factors associated with variation in left atrial size, finding that older age, hypertension, LV dilation and measures of obesity associate with larger LA volume. 7, 10–12 .…”
mentioning
confidence: 99%
“…In fact, LVH has been shown to be more than four times more likely in obese adolescents than non-obese adolescents (Odds ratio [OR] 4.51, 95%CI 2. 83-7.19) [24]. However, the welldemonstrated protective effect of overweight and class I-II obesity in the patient who has an existing diagnosis of HF, known as the Bobesity paradox,^should be remembered [22].…”
Section: Myocardial Remodelingmentioning
confidence: 96%